LOS GENERO S CORDAICARPUS GEINITZ, CORNUCARPUS ARBER y SAMAROPSIS GOEPPERT (SEMILLAS PLATISPERMICAS) EN EL NEOPALEOZOICO ARGENTINO (Ameghiniana, 2013)
Platyspennic seeds from the late Palaeozoic basins of central west Argentina are described. They were found in the Paganzo (Solea, Libertad, Arroyo Totoral, Lagares, Agua Colorada and Tupe Fonnations), Río Blanco (Cerro Agua Negra Fonnation) and the San Rafael (El Imperial Fonnation) basins. The following taxa have been described: Cornucarpus patagonicus (Feruglio) Correa da Silva & Arrondo. Cordaicarpus acuminatns nov. sp., C. cesarii nov. sp., C.famatil/el/sis nov. sp., C. sp. A, C. sp. B, C.? sp., Samaropsis cuerdai nov. sp .. S. nuñczii García, S. sp. A and S. sp. B. Most are stratigraphycally (late Carboniferous, early Pennian) and geographycalIy (central-west Argentina) restricted, except C. patagonicus. A list of fossil plants found in association is presented for each fonnation. Also, information on the taxonomy, stratigraphical and geographical distribution of Cordaicarpus, Cornucarpus and SamaropsIs species found in Argentina is summarized.